Recover recovery style from psychosis: a psychometric evaluation of the German version of the Recovery Style Questionnaire (RSQ). (2020) - Gruber, M.; Rumpold, T.; Schrank, B.; Sibitz, I.; Otzelberger, B.; Jahn, R.; Amering, M.; Unger, A.
Abstract: Aims: The way an individual handles the experience of psychosis, the so-called 'recovery style', has been shown to substantially affect long-term outcomes. The Recovery Style Questionnaire (RSQ) measures this psychological dimension. The aim of this study was to provide a validation of the German version of the RSQ and to raise awareness for recovery-oriented approaches. Methods: The RSQ was translated into German according to the guidelines of the WHO and patients were administered this questionnaire and measures of internalised stigma, psychotic symptoms, illness concept, empowerment, self-esteem and quality of life. Descriptive statistics were demonstrated to characterise the sample. Reliability was assessed in different forms: internal consistency, test–retest reliability and split-half reliability. Items were evaluated with descriptive data and item-total correlations. Convergent and discriminant validity were shown, and a confirmatory factor analysis was performed. In order to ameliorate the model, a post hoc model modification was done. Results: The sample consisted of 138 patients diagnosed with schizophrenia spectrum disorders (mean age: 35.7 years; 53.6% men; mean duration of illness: 20.6 years) with a mean RSQ overall percentage of 66.12 (s.d. ± 17.43%), mainly representing the categories 'mixed picture' and 'tends towards integration'. The reliability of the RSQ was acceptable with a Cronbach's α of 0.741 and a test–retest coefficient of 0.502. Item-total correlations were not acceptable for 27 of 39 items. Moderate evidence for convergent validity of the RSQ was found. Confirmatory factor analysis revealed that the 13-factor model with 39 items originally proposed was partially poorly replicated in the present sample ( χ 2 ratio to degrees of freedom ( χ 2 /df) of 1.732, Comparative Fit Index (CFI) of 0.585, Normed Fit Index (NFI) of 0.414, Tucker–Lewis Index (TLI) of 0.508, root mean square error of approximation (RMSEA) of 0.095). The RSQ was modified based on item-total correlations and path coefficients of the single items. The confirmatory factor analysis of the resulting one-factor model with 11 items showed adequate fit to the data ( χ 2 /df of 1.562, CFI of 0.936, NFI of 0.847, TLI of 0.910, RMSEA of 0.083) and demonstrated good model fit. Conclusions: Despite partially insufficient psychometric data of the original RSQ, the concept of recovery style is beneficial to psychiatric research and clinical practice. The underlying idea is valuable, and the questionnaire needs further development. Therefore, a short version of the RSQ is proposed.